ANALISA DAN PERANCANGAN SISTEM INFORMASI APLIKASI ABSENSI BERBASIS ONLINE DI PT.XYZ - Al Rasyid, Muhammad Fadhil; Ilmi, Miftahul; Suharyanto, Cosmas Eko (Program Studi Sistem Informasi Institut Indobaru Nasional, 2024)
The VB.NET-based employee attendance application is a system designed to record employee attendance, tardiness, leave, and absences in real-time using a simple form-based interface. This application aims to address issues in manual attendance systems, which are often inefficient and prone to data errors. By utilizing Visual Basic .NET as the programming language and Microsoft SQL Server as the database, this application enables accurate, secure, and easily accessible data recording. Key features include employee data management, attendance time recording, and daily and monthly attendance report generation directly through the application forms. Testing is conducted to ensure all features function according to user needs. The implementation of this application demonstrates improved operational efficiency and accuracy in attendance management. Furthermore, this application emphasizes data security and ease of use, ensuring that sensitive information is protected. The system is designed with scalability, allowing future enhancements like webbased access or integration with advanced tools. Thus, this system becomes an ideal solution for companies to effectively manage employee attendance data.